2018
DOI: 10.1159/000487675
|View full text |Cite
|
Sign up to set email alerts
|

Hypouricemic and Nephroprotective Effects of an Active Fraction from <b><i>Polyrhachis Vicina Roger</i></b> On Potassium Oxonate-Induced Hyperuricemia in Rats

Abstract: Background/Aims: The objective of this study is to evaluate the hypouricemic and nephroprotective effects of an active fraction from Polyrhachis vicina Roger (AFPR) in potassium oxonate-induced hyperuricemic rats. Methods: Hyperuricemia was induced by potassium oxonate in male rats. AFPR was orally administered to hyperuricemic rats for 12 consecutive weeks. Serum, liver and kidney samples were collected for effects and mechanism analysis. The levels of serum uric acid (SUA) were measured by the phosphotungsti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The ratio of omega-6/omega-3 was less than 5 in other edible insects, such as Clanis bilineata . This ratio meets the health requirements of human intake ( 13 ). An appropriate proportion of omega-6/omega-3 fatty acids exerts various bioactivities, including anticancer, anti-atherosclerotic, antithrombotic, anti-inflammatory, and antidiabetes activities, in humans ( 33 ).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The ratio of omega-6/omega-3 was less than 5 in other edible insects, such as Clanis bilineata . This ratio meets the health requirements of human intake ( 13 ). An appropriate proportion of omega-6/omega-3 fatty acids exerts various bioactivities, including anticancer, anti-atherosclerotic, antithrombotic, anti-inflammatory, and antidiabetes activities, in humans ( 33 ).…”
Section: Resultsmentioning
confidence: 78%
“…However, limited studies have examined the phenolic components of P. vicina . Previous studies have reported that P. vicina extracts exert hyperuricemia and exhibit anti-inflammatory and antitumor activities ( 12 , 13 ). Thus, the practice of P. vicina supplementation in wine has continued for many years in China or certain Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that there was a close correlation between serum urate and creatinine concentrations in gout patients [ 23 ]. Increases in serum BUN and creatinine indicate nephrotoxicity and cause renal damage in hyperuricemia [ 24 ]. Our results suggested that the addition of AE to AP therapy could prevent renal damage.…”
Section: Discussionmentioning
confidence: 99%
“…PO is most frequently used to set up animal models of hyperuricemia via suppressing uricase that converts UA to allantoin [ 22 ]. In this study, we successfully established PO-induced hyperuricemic mouse model, and evaluated the protective effect of WFA.…”
Section: Discussionmentioning
confidence: 99%